Álvaro Reis pastor, pregador e polemista: uma breve análise sobre seu discurso - Ribeiro, Ademir (2006)
This dissertation as its objective a short analysis of the polemic discourse of Alvaro Reis, as seen in part of one of his works, The Caldaic Origins of Bible. This text was initially written as a polemic debate with José Campos Novaes, a scholar of the times. We mean to analyze the first chapter, dealing with authenticity of the first five chapter of the Bible known as Pentateuch. Since our analyses has the Bible and its relation with the protestant context, as base of the discourse, we discuss the coming of the Protestants to the country, its cultural, political and religious context, as far as it is a par of Alvaro Reis s life. The research included his functions as minister and preacher of Brazilian Presbyterian Church. Through the readings of the work mentioned above, and one of his other words, The Spiritism, both part of his polemic discourses, we found the means of his function as a polemist and his refutations.